PENGEMBANGAN MODUL BERBASIS CREATIVE PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATERI SISTEM PEREDARAN DARAH KELAS XI MA NW SENYIUR - Mia Warni (Cocos Bio, 2026)
This study aims to determine the feasibility, practicality, and effectiveness of a Creative Problem Solving-based biology module on students’ creative thinking skills. The research and development process, using the Borg and Gall model, consists of six stages: 1. Initial information gathering, 2. Planning, 3. Development of the initial product, 4. Preliminary testing, 5. Product revision, and 6. Limited-scale testing. The preliminary test was conducted through a feasibility test involving subject matter experts and design experts, while the practicality test involved a biology teacher and 15 students. The limited-scale test was conducted on 38 students at MA NW Senyiur. The data collection methods used were questionnaires and tests. Data analysis employed quantitative descriptive analysis. Based on the results of the feasibility test, average scores of 89.3% and 97% were obtained, and the practicality test yielded averages of 97% and 2.79%, which fall within the “practical” category. The results of the effectiveness test of the Creative Problem Solving-based biology module in the experimental class fell into the “effective” category with an N-Gain of 0.71, while the control class achieved an N-Gain of 0.5, falling into the “moderately effective” category. This is because this learning model trains students to think creatively